Sense of coherence is associated with the presence of healthy lifestyles in the migrant population - Urzúa, Alfonso; Henríquez, Diego; Caqueo-Urízar, Alejandra; Salazar-Fernández, Tiare; Esquivel Rojas, María Fernanda; Díaz Vera, Rocío; Hoppe Chacón, Fernanda (Frontiers in Psychology, 2025)
BackgroundDespite the evidence of the sense of coherence (SOC) as a key factor in stress management and health promotion, there is little information about its connection with healthy lifestyles in migrant population.ObjectiveTo investigate the relationship between the variables SOC and Healthy Lifestyles in a south-south migrant population.Study designNon-experimental, cross-sectional and correlational study.MethodA total of 1,844 migrants living in Chile participated, selected through a non-probabilistic intentional sampling. The SOC and lifestyle were assessed by applying the FANTASTICO and SOC-13 instruments.ResultsSOC was positively correlated with lifestyle in the migrant population. Sex differences in SOC were identified, suggesting that men have greater access to resources. Age was also positively correlated with SOC and healthy lifestyle. Overall, the importance of considering the particularities of each group in health promotion in migration contexts is emphasized.ConclusionsThis research supports the hypothesis that a strong SOC is positively related to a healthy lifestyle in migrants. The differences found could be explained by sociocultural resources and norms, suggesting the importance of comprehensively addressing aspects related to the mental and physical health of the migrant population, especially in complex migratory contexts.